A Mother’s Struggle to Get Her Love in Vaughn’s Novel “The Price of Everything” - Diana Zuriati (LINGUA LITERA : journal of english linguistics and literature, 2017)
The purpose of this study was to know the reason of Giselle had to struggle to get her daughter’s love and the second reason was to know how the ways ingetting her daughter’s love. In analyzing this novel, the researcher used a qualitative study using descriptive method. Based on the results of the study, thefirst reason that Giselle had the right to get the love of her daughter because she was the mother who gave birth to her, this happened because the pressure shegot from her husband. And the second reason because she was getting pressure from her step-sister in-law who was also a lover of her husband. For this reason,Giselle tried to get her daughter’s love. The results of the second study was how the ways to get love daughter’s love, that she had to fight her step-sister in-lawand how she convinced her daughter that all this were told by Alexandra about her was not true. Finally, Giselle succeeded to get her daughter’s love. This wasa clear description that a mother's love for her child would never extinguish even though her child ever hurt her because a mother had a true love.